CBCT Evaluation of the Root Canal Filling Removal Using D-RaCe, ProTaper Retreatment Kit and Hand Files in curved canals - Madani, Zahra Sadat; Simdar, Narges; Moudi, Ehsan; Bijani, Ali (Iranian Endodontic Journal, 2014)
Introduction: The aim of the present in vitro study was to evaluate the efficacy of D-RaCe, ProTaper retreatment kit and hand H-files in removal of obturating materials (OM) from the curved root canals using cone-beam computed tomography (CBCT). Materials and methods: Sixty extracted molars were prepared and obturated. The samples were divided into three groups (n=20). In each group the OM was removed using hand H-files, D-RaCe and ProTaper retreatment kit. All the samples underwent CBCT imaging. The amount of OM was evaluated in CBCT sagittal cross-sections and scored. The maximum concentration of residual OM was recorded. The duration of the procedure (including the required time for reaching working length=T1 and total working time=TT) and procedural errors were also recorded. Data were analyzed using one-way ANOVA, Tukey’s post hoc test, Fisher’s exact test and Kruskal-Wallis test. The level f significance was set at 0.05. Results: No significant differences were observed in the residual OM among the three groups. T1 and TT were not significantly different in all the groups. There were no significant differences in concentration of OM between the groups (P<0.05). In relation to procedural errors, 4 and 5 cases of file fracture were recorded in the ProTaper and D-RaCe groups, respectively, with no significant differences. Conclusion: Rotary and hand files had similar efficacy in removing root canal filling materials but instrument fracture occurred more frequently in rotary files.